21st Century Advanced Carbon Materials for Engineering Applications A Comprehensive Handbook - Ikram, Mujtaba; Maqsood, Asghari (IntechOpen, 2021)
Advanced carbon materials such as graphene, fullerenes, hierarchical carbon, and carbon nanotubes (CNTs) have exceptional physical properties, making them useful for several applications in fields ranging from energy and industry to electronics and drug delivery. This book includes comprehensive information on fabrication, emerging physical properties, and technological applications of advanced carbon materials. Over three sections, chapters cover such topics as advanced carbon materials in engineering, conjugation of graphene with other 2D materials, fabrication of CNTs and their use in tissue engineering and orthopaedics, and advanced carbon materials for sustainable applications, among others.